A dual center and dual vendor comparison study of automated perfusion‐weighted phase‐resolved functional lung magnetic resonance imaging with dynamic contrast‐enhanced magnetic resonance imaging in patients with cystic fibrosis. (5th April 2022) - Behrendt, Lea; Smith, Laurie J.; Voskrebenzev, Andreas; Klimeš, Filip; Kaireit, Till F.; Pöhler, Gesa H.; Kern, Agilo L.; Gonzalez, Cristian Crisosto; Dittrich, Anna‐Maria; Marshall, Helen; Schütz, Katharina; Hughes, Paul J. C.; et al.
Abstract: For sensitive diagnosis and monitoring of pulmonary disease, ionizing radiation‐free imaging methods are of great importance. A noncontrast and free‐breathing proton magnetic resonance imaging (MRI) technique for assessment of pulmonary perfusion is phase‐resolved functional lung (PREFUL) MRI. Since there is no validation of PREFUL MRI across different centers and scanners, the purpose of this study was to compare perfusion‐weighted PREFUL MRI with the well‐established dynamic contrast‐enhanced (DCE) MRI across two centers on scanners from two different vendors. Sixteen patients with cystic fibrosis (CF) (Center 1: 10 patients; Center 2: 6 patients) underwent PREFUL and DCE MRI at 1.5T in the same imaging session. Normalized perfusion‐weighted values and perfusion defect percentage (QDP) values were calculated for the whole lung and three central slices (dorsal, central, ventral of the carina). Obtained parameters were compared using Pearson correlation, Spearman correlation, Bland–Altman analysis, Wilcoxon signed‐rank test, and Wilcoxon rank‐sum test. Moderate‐to‐strong correlations between normalized perfusion‐weighted PREFUL and DCE values were found (posterior slice: r = 0.69, p < 0.01). Spatial overlap of PREFUL and DCE QDP maps showed an agreement of 79.4% for the whole lung. Further, spatial overlap values of Center 1 were not significantly different to those of Center 2 for the three central slices ( p > 0.07). The feasibility of PREFUL MRI across two different centers and two different vendors was shown in patients with CF and obtained results were in agreement with DCE MRI.